The plant-specific TFIIB-related protein, pBrp, is a general transcription factor for RNA polymerase I - Imamura, Sousuke (Nature Publishing Group, 2008)
TFIIB and BRF are general transcription factors (GTFs) for eukaryotic RNA polymerases II and III, respectively, and have important functions in transcriptional initiation. In this study, the third type of TFIIB-related protein, pBrp, found in plant lineages was characterized in the red alga Cyanidioschyzon merolae. Chromatin immunoprecipitation analysis revealed that CmpBrp specifically occupied the rDNA promoter region in vivo, and the occupancy was proportional to de novo 18S rRNA synthesis. Consistently, CmpBrp and CmTBP cooperatively bound the rDNA promoter region in vitro, and the binding site was identified at a proximal downstream region of the transcription start point. α-Amanitin-resistant transcription from the rDNA promoter in crude cell lysate was severely inhibited by the CmpBrp antibody and was also inhibited when DNA template with a mutated CmpBrp–CmTBP binding site was used. CmpBrp was shown to co-immunoprecipitate and co-localize with the RNA polymerase I subunit, CmRPA190, in the cell. Thus, together with comparative studies of Arabidopsis pBrp, we concluded that pBrp is a GTF for RNA polymerase I in plant cells.